(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2019)
The current paper seeks to illustrate the conflict between habituation and moral autonomy and explain the Islamic view in this regard. The methodology of this research is qualitative and Islamic classical sources have been used to further elucidate Islam’s stance, as we have referred to some articles and resources to understand the concept of habituation method and its contradictions with moral autonomy. The achievement of the paper is realising the contradiction between the habituation method and moral autonomy and habituation’s incompatibility with the rational growth and development of the youth which is the goal of Islamic education. Therefore, this method cannot be accepted in Islamic moral education. On the other hand, there are some narratives in the Islamic sources that apparently have recommended this method, so another important achievement of the article is the proper interpretation of these narratives, presented for the first time. According to this interpretation, these narratives do not recommend the habituation method, but rather the continuity and maintenance of the action. Therefore, there is no disapproval in Islamic sources in this regard, and these sources reject the use of this method in moral education. The paper concludes by saying that the habituation method is not an Islamic method of education, and Islamic narrations have not recommended it. This paper comes with a suggestion that education scholars and policy makers need to extract other methods from the Islamic sources and devise them according to scientific findings instead of using this method.